Real-Time GPS/GPRS Based Vehicle Tracking System (International Journal of Engineering and Computer Science, 2015)
Designing a vehicle tracking system which can work effective, accurate and reliable is emerging in many areas. Such system is commonly used GPS technology to determine location of the vehicle. It can be used to track a vehicle or fleet of vehicles and get information related to current location of the vehicles. High required operating cost of the vehicle tracking systems, including hardware and software requirements, usually, prevent these systems from being widespread applicable. In this paper a vehicle tracking system based on GPS and GPRS is proposed. The location of the vehicle is retrieved using embedded GPS sensor. A modified coding method is used to encode and compress location data before it is sent to offer cost effective usage of network traffic. The privacy of the transmitted data is guaranteed using a simple security mechanism. The encoded and encrypted location data then send to tracking server using GPRS technology. The authorized user can track a vehicle using a secure web interface.